Antioxidant Activity of Stannous Complexes Containing Amide Functionality - Thomas, Raji; Pardasani, Pushpa (Universitas Jenderal Soedirman, 2026)
ABSTRACT. Oxidative stress induced by free radicals is closely associated with aging and various degenerative diseases, prompting the search for efficient antioxidant systems. Metal chelation is known to enhance the biological activity of organic ligands by altering their electronic and redox characteristics. In this study, penta- and tetra-coordinated stannyl complexes of N,N′-bis(2-pyridyl)pyridine-2,6-dicarboxamide (H₂L₁) and N-(pyridine-2-yl)picolinamide (HL₂) were synthesized and evaluated for their antioxidant activity using the DPPH free radical scavenging assay. Penta and tetra coordinated stannyl derivatives of N, N'-Bis(2-pyridyl)pyridine-2,6-dicarboxamide (H2L1) and N-(pyridine-2-yl)picolinamide (HL2) have been synthesized by the reported procedure and selected for the antioxidant studies. The free radical scavenging activity of ligands and the metal complexes have been analyzed by means of their interaction with stable free radical 1, 1-diphenyl-2-picrylhydrazyl (DPPH). The molecular structures and electronic properties of complexes and the mechanism involved in the scavenging activity were well analyzed by GAUSSIAN 03 suit of programs. Keywords: Amide complexes, computational, DPPH, free radical